Selective-area growth and controlled substrate coupling of transition metal dichalcogenides. (28th April 2017) - Bersch, Brian M; Eichfeld, Sarah M; Lin, Yu-Chuan; Zhang, Kehao; Bhimanapati, Ganesh R; Piasecki, Aleksander F; Labella, Michael; Robinson, Joshua A
Abstract: Developing a means for true bottom-up, selective-area growth of two-dimensional (2D) materials on device-ready substrates will enable synthesis in regions only where they are needed. Here, we demonstrate seed-free, site-specific nucleation of transition metal dichalcogenides (TMDs) with precise control over lateral growth by utilizing an ultra-thin polymeric surface functionalization capable of precluding nucleation and growth. This polymer functional layer (PFL) is derived from conventional photoresists and lithographic processing, and is compatible with multiple growth techniques, precursors (metal organics, solid-source) and TMDs. Additionally, we demonstrate that the substrate can play a major role in TMD transport properties. With proper TMD/substrate decoupling, top-gated field-effect transistors (FETs) fabricated with selectively-grown monolayer MoS2 channels are competitive with current reported MoS2 FETs. The work presented here demonstrates that substrate surface engineering is key to realizing precisely located and geometrically-defined 2D layers via unseeded chemical vapor deposition techniques.